Waste Polyethylene Terephthalate (PET) as a Partial Replacement of Aggregates in Sustainable Concrete - Lukman Abubakar; Nusrat Yeasmin; Arjak Bhattacharjee (Construction Materials)
Concrete use is enhanced daily due to infrastructure development, but it has adverse impacts on the environment. Modern lifestyles have led to the increased use of plastic, and, for households, polyethylene terephthalate (PET) plastics are used. However, PET is non-biodegradable and causes adverse impacts on the environment and marine health. So, there is a need to minimize the amount of plastic waste by finding an alternative use for the waste. Our study focuses on creating sustainable concrete by utilizing PET-based plastic waste as a partial substitution for aggregates, aiming to use this concrete for various low-load-bearing construction applications. From our phase analysis study, no adverse effects were found on cement phase formation. We also found that up to 10 wt.% PET incorporation leads to acceptable compressive strength reduction as per ASTM guidelines. To enhance adhesion, the PET was roughened, and, from FESEM, we found effective adhesion of PET waste into the cement matrix. We believe that this sustainable concrete will not only contribute to waste reduction but also promote eco-friendly construction material development.